1983
DOI: 10.1002/nur.4770060304
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the Early Phase of Rehabilitation Following Aortocoronary Bypass Surgery

Abstract: Physical and psychosocial functioning of 30 male patients prior to and 3 months following aortocoronary bypass surgery were compared. Relationships between rehabilitation outcome and selected physical, psychosocial, and health care system variables were examined. Although patients' perceptions of their health improved after surgery, there was little improvement in physical and psychosocial functioning, and vocational functioning declined. When the outcome variables were regressed on their possible explanatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The method has not been utilized in pain patients, and has the disadvantage of being expensive. In patients who underwent coronary bypass surgery, energy expenditure on postoperative leisure activities has been reported to be associated to fear of injury (O'Connor, 1983). Alternatively, quanti®cation of physical activity can be done with activity diaries (Fordyce, 1976) or with the more advanced automated activity monitors (Bussman et al, 1998).…”
Section: Pain-related Fear and Physical Performancementioning
confidence: 99%
“…The method has not been utilized in pain patients, and has the disadvantage of being expensive. In patients who underwent coronary bypass surgery, energy expenditure on postoperative leisure activities has been reported to be associated to fear of injury (O'Connor, 1983). Alternatively, quanti®cation of physical activity can be done with activity diaries (Fordyce, 1976) or with the more advanced automated activity monitors (Bussman et al, 1998).…”
Section: Pain-related Fear and Physical Performancementioning
confidence: 99%
“…In fact, spouse support had negative effects on physical activity, perhaps because the spouse assumed an enforcer role vis-his the regimen. O'Connor (1983) found that perceptions of health and leisure activities of patients undergoing coronary artery bypass surgery were affected negatively by a spouse's fear of injury. Further, Schafer McCaul and Glasgow (1986) found that adults with diabetes who perceived more negative or nonsupportive behaviors from their families were less likely to adhere to their diabetic regimen and had poorer diabetes control than did those reporting fewer nonsupportive family behaviors.…”
Section: Supporting Families During Chronic Illnessmentioning
confidence: 99%
“…Despite the studies mentioned above, much of the research on the psychological impact of cardiac surgery has excluded women in general (Auerbach, 1973;Fontana, Kerns, Rosenberg & Colonese, 1989 ;Freeman, Fleece, Folks, Cohen-Cole & Waldo, 1984;Horgan, Davies, Hunt, Westlake & Mullerworth, 1984;Kulik & Mahler, 1989;O'Connor, 1983) or specifically women of childbearing age (Folks, Blake, Fleece, Sokol & Freeman, 1986;Folks, Blake, Freeman, Sokol & Baker, 1988;Sokol et uL., 1987). Other studies have involved so few female subjects that it is difficult to interpret the results (Kos-Munson e t a /., 1988).…”
mentioning
confidence: 99%
“…Previous studies have suffered from a number of other methodological shortcomings, including an exclusion of older individuals (Folks e t a/., 1986;Folks e t a/., 1988;Freeman e t a/., 1984;Jenkins, Stanton, Savageau, Denlinger & Klein, 1983 ; Sokol e t a/., 1987), non-standardized measures of depression and anxiety (Blachly & Blachly, 1968;Rabiner et a/., 1975), failure to obtain baseline measures (Fontana e t a/., 1989), use of retrospective mood ratings (Blachly & Blachly, 1968;O'Connor, 1983), inclusion of illiterate subjects who required special assistance to complete the testing (Sokol e t a/., 1987), and highly selected samples (O'Connor, 1983).…”
mentioning
confidence: 99%